Ice-Cream Substitute for Patients With Kidney Failure - Iocca, Abby; Bardwell, Amy M; Schumacher, Julie R; Barnes, Jennifer L (Journal of renal nutrition, 2022)
Quality of life for patients with kidney failure is less than similar-aged, general population counterparts. A large part of the decrease in quality of life is from the change of diet and nutritional restrictions. One way to combat this decrease in quality of life is through oral nutrition supplements. An ice-cream substitute product was developed for patients with kidney failure on peritoneal dialysis. The product consisted of an ice-cream-like base of rice milk, egg whites, evaporated coconut milk, sugar, and vanilla bean paste. Two flavors were then created: cinnamon and lemon. Both flavors were tested subjectively and objectively. Sensory taste testing was with peritoneal dialysis patients using a Likert scale ballot with a comment section. Texture analysis was completed using a CT3 Brookfield texture analyzer. The results from the sensory testing (taste, texture, overall acceptability) and the texture analysis were analyzed using paired-samples t-tests. Nutritional analysis for the product was calculated. The sensory test of taste, texture, and overall acceptability between the two flavors was not found to be statistically different between the cinnamon and lemon. Similarly, the objective results were also not statistically significant between the two flavors. Based on the nutritional analysis, both the lemon and the cinnamon flavors were found to be "good" sources of protein when compared with the Food and Drug Administration's definition of a "good" source of protein. In addition, patients found the sensory aspects of both flavors to be slightly to moderately likable.